THE INFLUENCE OF TAX SOCIALIZATION, TAX KNOWLEDGE AND THE APPLICATION OF THE E-FILLING SYSTEM ON TAXPAYER COMPLIANCE IN STUDENTS AT UNIVERSITAS PAMULANG - Sheila Ardianti; Intan Rahma Sari (Transpublika Publisher, 2023)
Taxation serves as the principal source of revenue for countries and plays a crucial role in promoting community welfare during the development process. Over time, the number of taxpayers has been steadily increasing, leading to a corresponding rise in tax revenue. This research aims to investigate the impact of tax socialization, tax knowledge, and the implementation of the e-filing system on taxpayer compliance. The study focuses on students enrolled in the accounting program at Pamulang University. A sample of 105 students from the accounting program at Pamulang University participated in the study, and primary data were collected through the distribution of questionnaires to the respondents. Multiple linear regression analysis was utilized to analyze the data. The findings of the study indicate the following: 1) Tax socialization significantly influences taxpayer compliance, as evidenced by an F statistic of 34.985 with a significant value of 0.000. 2) Tax socialization positively impacts taxpayer compliance with a significance level of 0.003. 3) Tax knowledge, on the other hand, does not significantly affect taxpayer compliance, as indicated by a significance level of 0.691. 4) The application of the e-filing system has a positive and significant effect on taxpayer compliance. 5) When considered together, tax socialization, tax knowledge, and the application of the e-filing system have a collective significant effect of 0.000 on taxpayer compliance among students at Pamulang University.